1995
DOI: 10.1029/95ja01524
|View full text |Cite
|
Sign up to set email alerts
|

Global numerical simulation of the growth phase and the expansion onset for a substorm observed by Viking

Abstract: We report the first global magnetohydrodynamic (MHD) simulation of an actual magnetospheric substorm, which was recorded by the Viking spacecraft on October 19, 1986. The simulation is driven by IMP 8 solar wind parameters measured upstream of the Earth's bow shock. The substorm, which had expansion onset at 1132 UT, was caused by a brief period of southward interplanetary magnetic field (IMF) and two weak solar wind shocks. The simulation model includes a self-consistent auroral ionospheric conductance depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
156
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 154 publications
(162 citation statements)
references
References 17 publications
5
156
1
Order By: Relevance
“…A recent focus of MHD investigations is the study of of the magnetic cloud that forms, and CME plasma propermagnetospheric "events." In these simulations the observed upstream solar wind conditions to are used to "drive" the magnetosphere-ionosphere system, and numerical predictions are compared with ground based or satellite observations [Fedder et al, 1995b[Fedder et al, , 1998Raeder et al, 1998]. In adties.…”
mentioning
confidence: 99%
“…A recent focus of MHD investigations is the study of of the magnetic cloud that forms, and CME plasma propermagnetospheric "events." In these simulations the observed upstream solar wind conditions to are used to "drive" the magnetosphere-ionosphere system, and numerical predictions are compared with ground based or satellite observations [Fedder et al, 1995b[Fedder et al, , 1998Raeder et al, 1998]. In adties.…”
mentioning
confidence: 99%
“…Inner zone flux changes are not followed because of the L=2.3 inner boundary of the MHD simulation. Electric and magnetic fields are mapped to the ionosphere assuming Hall and Pederson conductivities which evolve in time with magnetic fieldaligned currents, simulating auroral ionization (Fedder et al, 1995). No plasmasphere was included for these long time scale runs, which require an evolving plasmasphere, in contrast to simulations of the rapid March 24, 1991 injection event, where the plasmasphere was characterized by initial planetary magnetic activity in dex Kp (Moore et al, 1987).…”
Section: Simulationsmentioning
confidence: 99%
“…The Lyon-FedderMobarry (LFM) simulation model [Fedder et al, 1995;Lyon et al, 1998] has been used to examine several substorm events, and the results have shown that the code reproduces well the observed main sequence of events during substorms. The magnetospheric output obtained from simulations driven by actual solar wind data is then used as input into the ionosphere.…”
Section: Introductionmentioning
confidence: 99%